Role of social business in women entrepreneurship development in Bangladesh: Perspectives from Nobin Udyokta projects of Grameen Telecom Trust - Farhana Ferdousi; Parveen Mahmud (Journal of Global Entrepreneurship Research, 2019)
Social business is a growing phenomenon in the emerging economy due to its appeal toward reducing social problems from the society. Women's, especially rural women's, economic activities are mainly confined to the household chores because of the existing patriarchal norms of the society. Social businesses, through providing equity funds, are creating opportunities for the women to pursue entrepreneurial career. This study attempted to analyze the role of social business for developing women entrepreneurship. Primary data were collected from 28 women Nobin Udyokta (new entrepreneurs) and four key informant interviews. The study showed that social business fund plays an important role toward women entrepreneurship development through providing financial (social business fund), human (formal or informal training), and social capital (network) to the women entrepreneurs which is necessary for sustainable entrepreneurship development. Therefore, government and non-government organizations as well as private sectors were suggested to come forward to provide more social business funds and build supportive environment for the women entrepreneurs.
Keywords: 650; Gender equality; Grameen Telecom Trust; Social business fund; Sustainable development goals; women empowerment; and Women entrepreneurship